Illiberal Reformers: Race, Eugenics and American Economics in the Progressive Era - Bishop, Wesley R. (Labour / Le Travail, 2016)
The article reviews the book, "Illiberal Reformers: Race, Eugenics and American Economics in the Progressive Era," by Thomas C. Leonard.